Study of prevalence of thyroid dysfunction in type 2 diabetes mellitus - Singh, Raj K.; Mittal, Mahim; Singh, Amit; Kumar, Ajay (International Journal of Research in Medical Sciences, 2018)
Background: Type 2 diabetes mellitus (T2DM) is associated with increased incidence of thyroid dysfunction (TD). The coexistence of thyroid dysfunction in T2DM patient is an important barrier in achieving treatment goal. The study regarding prevalence of TD in T2DM has not been done in patients of Eastern Uttar Pradesh. The present study was aimed to know the prevalence of thyroid dysfunction in T2DM in patients of Eastern Uttar Pradesh. Methods: This is an observational cross sectional prevalence study of thyroid dysfunction in 250 diagnosed T2DM patients deleat diagnosed based on ADA criteria attending the department of medicine Baba Raghav Das Medical College, Gorakhpur, Uttar Pradesh, Study was India, done over a period of 1 year. Thyroid dysfunction was classified on the basis of ATA criteria. All subjects underwent a detailed history, clinical examination and relevant biochemical tests. Results: The prevalence of thyroid dysfunction in T2DM patients was found to be 20.4% in this study. Conclusions: The prevalence of thyroid dysfunction was found to be higher in type 2 diabetes mellitus patients in comparison to general population as mentioned in different literature.